Kajian Sifat Fisikokimia Permen Jelly Jeruk Kalamansi dengan Perbedaan Jenis dan Konsentrasi Bahan Pemanis - Chairanil Fadhilah; Merynda Indriyani Syafutri (Seminar Nasional Lahan Suboptimal, 2021)
Fadhilah C, Syafutri MI.  2021. Study of physicochemical properties of calamondin jelly candy with difference of types and sweetener concentrations. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 459-464. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The use of calamondin is still limited to food ingredients and the food industry. Some studies had tried to process it into a powder product and also hard candy, so it has the potential to be processed into jelly candy. This study aimed to study the physicochemical properties of calamondin jelly candy with the difference of types and sweetener concentrations. This study used a non-factorial Completely Randomized Design (CRD). The factor used was sweetener which consisted of 9 levels (granulated sugar 20%, 30%, 40%, palm sugar 20%, 30%, 40%, and honey 20%, 30%, 40%). The parameters observed included physical properties (hardness) and chemical properties (reducing sugar, water, and ash content). The results showed that the sweetener had significant effects on increasing the ash content, but had no significant effect on the hardness, reducing sugar content, and water content. The use of 30% granulated sugar was the best treatment for calamondin jelly candy because it approached SNI (2008) based on parameters of water content, ash content, and reducing sugar content.